INTEGRATION OF GREEN TARGET COST SYSTEM AND VALUE ENGINEERING IN ACHIEVING SUSTAINABLE DEVELOPMENT. (AN APPLIED STUDY IN THE STATE COMPANY FOR THE FERTILIZER INDUSTRY, BASRA, IRAQ) - Abdulkareem Abdulghani Oudah; Sahar Nazar Abdulsalam (Scholar Express Journals, 2022)
The research aims to demonstrate the role of modern cost-effective technologies in reducing costs and producing green products, as the green product is based on several dimensions (it works to reduce pollution rates, avoids the use of toxic substances harmful to the environment, uses renewable energy, reduces the use of natural resources and preserves them). In general, a green product is designed or manufactured in a way that minimizes the environmental impact involved in its production, distribution and consumption, the main challenge in creating sustainable green products by integrating the product's environmental and traditional features. By integrating this technology with value engineering technology, which operates a systematic process of technical evaluation of a product to eliminate unnecessary costs and add value while maintaining or re-improving quality, scope and performance, the main procedure in implementing value engineering technology is to conduct analyzes during the design phase of new and modified products. From the point of view of the consumer, and that this analysis will diagnose the basic consumer details, the value engineering technique focuses on improving customer satisfaction with the product, material or process that has been studied by identifying their needs and requirements and working to implement their desires
Keywords: Green Target Cost; Green Product,; Value Engineering; Sustainable Development